Validating subjective ratings with wearable data for a nuanced understanding of load-recovery status in elite endurance athletes - Spetz, L.; Rogestedt, J.; Nilsson, R.; Mattsson, C. M.; Larsen, F. J. (Sports Medicine - Open, 2025)
Background The emergence of wearable technology offers enhanced real-time health management, including sleep, recovery, and exercise optimization. Despite their potential to monitor load-recovery parameters in elite athletes, the selection, combination, and interpretation or reliance of metrics in relation to perceived impact remain unclear.